Conflict in World Heritage Sites of Kathmandu Valley: A Case Study on the Conservation of Private Houses in Three Durbar Squares - Maharjan, Monalisa (Nepal Tourism and Development Review, 2013)
Conflict between heritage management authorities and the local residents has been critical to sustainable management of the World Heritage Sites (WHS) in Kathmandu Valley. This paper attempts to find out the reasons of such conflict by analyzing the facets of prevalent non-compliance of rules and regulations in Kathmandu Valley’s three World Heritage Sites: Hanuman Dhoka, Patan and Bhaktapur Durbar Squares. This is a qualitative analysis of perceptions, understanding and interests of the local people and the heritage management authorities. The paper also reviews the existing national and international policy provisions on conservation of WHS and makes special notes about the conservation of private houses in the WHS. Cases were selected using snow-ball sampling technique. Structured interviews were conducted with key informants including concerned government officials and the local residents. The findings include such reasons of non-compliance of WHS regulations as overlapping and unclear roles of multiple institutions involved in the management of the WHS, lack of public participation in decision making, inadequate economic incentives to locals, ineffective implementation of compliance mechanisms. DOI: http://dx.doi.org/10.3126/ntdr.v2i1.7381 Nepal Tourism and Development Review Vol.2(1) 2012 87-104